2002
DOI: 10.1093/toxsci/68.1.174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in Utero Exposure to the Organophosphate Insecticide Fenitrothion on Androgen-Dependent Reproductive Development in the Crl:CD(SD)BR Rat

Abstract: Fenitrothion [0,0-dimethyl-O-(4-nitro-m-tolyl) phosphorothioate] is an organophosphate insecticide that has been shown to have antiandrogenic activity using in vitro and in vivo screening assays. Studies were performed to evaluate the ability of fenitrothion to disrupt androgen-dependent sexual differentiation in the male rat. Pregnant Crl:CD(SD)BR rats were administered fenitrothion by gavage at 0, 5, 10, 15, 20, or 25 mg/kg/day ( n = 6-11/group) from gestation day (GD) 12 to 21. Maternal toxicity was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 43 publications
5
34
1
1
Order By: Relevance
“…There is insufficient evidence to assess the risk of tested pesticides to human health because of a lack of data. However, to our knowledge, all of the pesticides (with the possible exception of fenitrothion; Okahashi et al 2005;Turner et al 2002) identified as in vitro AR antagonists in our study have also been reported to have anti androgenic effects in vivo in animal models (Anway et al 2006;Gray et al 1999;Lambright et al 2000;McIntyre et al 2002;Ostby et al 1999;Sinha et al 2001;Taxvig et al 2007;Uzumcu et al 2004;Vinggaard et al 2005). We also identified 7 compounds that appeared to be androgenic because they stimulated activity in the absence of DHT.…”
Section: Discussionmentioning
confidence: 54%
“…There is insufficient evidence to assess the risk of tested pesticides to human health because of a lack of data. However, to our knowledge, all of the pesticides (with the possible exception of fenitrothion; Okahashi et al 2005;Turner et al 2002) identified as in vitro AR antagonists in our study have also been reported to have anti androgenic effects in vivo in animal models (Anway et al 2006;Gray et al 1999;Lambright et al 2000;McIntyre et al 2002;Ostby et al 1999;Sinha et al 2001;Taxvig et al 2007;Uzumcu et al 2004;Vinggaard et al 2005). We also identified 7 compounds that appeared to be androgenic because they stimulated activity in the absence of DHT.…”
Section: Discussionmentioning
confidence: 54%
“…Following screening assays showing that fenitrothion acts as an androgen receptor (AR) in in vitro (HepG2 human hepatoma liver cells transfected with human AR and an AR-dependent luciferase reporter gene) and in vivo (male rat Hershberger assay) (407), 0, 5, 10, 15, 20, or 25 mg/kg fenitrothion was administered via oral gavage to pregnant rats on gestation days 12 through 21, and effects on male development were assessed (408). Maternal toxicity (tremors and decreased body weight) and fetal death (decreased number of pups born alive) occurred at 20 and 25 mg/kg/day.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Fenitrothion was found to act as an antiandrogen under both in vitro and in vivo assays and competitively antagonized human androgen receptors (Tamura et al, 2001;Turner et al, 2002). On the other hand, some organophosphate pesticides have been shown to alter normal endocrine function by inhibiting steroid hormones biosynthesis such as dichlorvos, dursban, diazinon and chlorpyrifos (Civen and Brown, 1974;Civen et al, 1977).…”
Section: Introductionmentioning
confidence: 99%